2011 Joint Workshop on Hands-Free Speech Communication and Microphone Arrays 2011
DOI: 10.1109/hscma.2011.5942377
|View full text |Cite
|
Sign up to set email alerts
|

Model-based approaches to handling additive noise in reverberant environments

Abstract: Model-based approaches to handle additive and convolutional noise have been extensively investigated and used. However, the application of these approaches to handling reverberant noise has received less attention. This paper examines the extension of two standard adaptation/compensation approaches to handling reverberant noise. The first is an extension of vector Taylor series (VTS) compensation, reverberant VTS, where a mismatch function representing reverberant noise is used. The second scheme modifies cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…As expected, these results do not differ much between the two considered observation models and compare favorably with the results presented in [9]. Briefly looking at the recursive variants of the observation models, we observed that they again performed slightly worse than the non-recursive variants (best results with 41.67% and 42.35% for the BFE-TI and the BFE-TV, respectively).…”
Section: ) Presence Of Reverberation and Noisesupporting
confidence: 88%
See 3 more Smart Citations
“…As expected, these results do not differ much between the two considered observation models and compare favorably with the results presented in [9]. Briefly looking at the recursive variants of the observation models, we observed that they again performed slightly worse than the non-recursive variants (best results with 41.67% and 42.35% for the BFE-TI and the BFE-TV, respectively).…”
Section: ) Presence Of Reverberation and Noisesupporting
confidence: 88%
“…Using interacting sub-models, the predictive PDF may be approximated by the following weighted sum of submodel specific predictive PDFs: (9) Here, indicates the index of the active submodel at time instant . Due to the definition of our state vector in (5), the sub-model specific PDF is completely determined by the PDF , which is approximated by (10) (11) In (10), denotes a GAUSSIAN PDF with mean vector and covariance matrix .…”
Section: A a Priori Speech Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Model-based approaches have also been extended to deal with the reverberant noise, e.g., in [7], [8] and [9], acoustic models are compensated using PMC. In [10], Reverberant VTS (RVTS) was proposed, where model-based VTS compensation was extended to handle the reverberant noise, as well as the background noise. RVTS allows the compensation formula for all the model parameters to be defined, and the parameters of the reverberant noise model can be estimated using maximum likelihood (ML) criterion.…”
Section: Introductionmentioning
confidence: 99%